The Activities of the Company of the Ukrainian Insurgent Army Roman Hrobelski “Brodycz” between 1944 and 1947 - Богдан Гальчак; Властіміл Ондрак (Історико-політичні проблеми сучасного світу)
The aim of the publication is to present the history of the Ukrainian Insurgent Army (UIA) company, whose commander was Roman Hrobelski (pseudonym “Brodycz”) in 1946-1947. The company was founded in 1944. It was part of the battalion commanded by Wasyl Mizerny (pseudonym “Ren”). The first commander of the company was a partisan named “Jar”. In the summer of 1945, Franc Hryhorowycz (pseudonym “Didyk”) took over the command. In April 1946, Roman Hrobelski was established as the new commander. In October 1946, the company of “Brodycz” moved to the area of Gorlice and Nowy Sącz poviats. In the new area of operation, the company of “Brodycz” operated until September 1947. Roman Brodycz's unit became the westernmost fighting unit of the UIA. The partisans survived the winter of 1946/1947 peacefully. The local Ukrainian population supplied them with food. The Polish communist authorities were primarily occupied with fighting the Polish anti-communist underground, which was active in the Gorlice and Nowy Sącz poviats. In 1947, however, the Polish underground was destroyed. The communist authorities directed large forces of the army and security organs against the UIA. In order to avoid manhunts organized by the Polish army, the „Brodycz” company often crossed the border cordon to the Czechoslovak side. In April 1947, Operation “Wisła” began. The Ukrainian population was displaced from their villages, deported to the western and northern territories of the Polish state and resettled forcibly in large dispersion. In June 1947, Operation “Wisła” also covered the poviats of Gorlice and Nowy Sącz. The Ukrainian population was almost completely displaced from this area. The deportation of the Ukrainian population deprived the branch of the company of „Brodycz” facilities. In September 1947, Roman Hrobelski's unit attempted to move to the West. During the passage through Czechoslovakia, 34 partisans were captured or killed. 53 partisans from the “Brodycz” company reached the West.